Garlic and sapphires [book club bag] : the secret life of a critic in disguise - Reichl, Ruth (Penguin Press, 2005)
Ruth Reichl, world-renowned food critic and former editor in chief of Gourmet magazine, knows a thing or two about food. She also knows that as the most important food critic in the country, you need to be anonymous when reviewing some of the most high-profile establishments in the biggest restaurant town in the world<U+2014>a charge she took very seriously, taking on the guise of a series of eccentric personalities. In Garlic and Sapphires, Reichl reveals the comic absurdity, artifice, and excellence to be found in the sumptuously appointed stages of the epicurean world and gives us<U+2014>along with some of her favorite recipes and reviews<U+2014>her remarkable reflections on how one<U+2019>s outer appearance can influence one<U+2019>s inner character, expectations, and appetites, not to mention the quality of service one receives.